2018
DOI: 10.1002/iub.1735
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin‐B2 enriched fraction of cinnamon acts as a proteasome inhibitor and anti‐proliferative agent in human prostate cancer cells

Abstract: Altered activity of the proteolytic machine-the 26S proteasome is observed in many disease conditions. Hence, either inhibition or activation of the 26S proteasome is thought to be a novel therapy for treatment of certain diseases such as cancer and neurodegenerative disorders. In this study, we tested the potential of cinnamon and one of its active ingredients, procyanidin-B2 (PCB2), in inhibiting the catalytic activities of the proteasome and suppressing prostate cancer cell growth. Proteasome activities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Procyanidin B2 (epicatechin-(4β-8)-epicatechin; PB2), a phenolic compound, primarily exists in common fruits, including red grapes, cocoa, lindera aggregate and cinnamon (22). PB2 isolated from cinnamon can significantly decline cell viability and accelerate apoptosis in prostate cancer cells, and the proapoptotic effect of PB2 might be associated with caspase-3 activity (23). PB2 is a bioactive component and a potent antioxidant for restoring and maintaining homeostasis (24).…”
Section: Introductionmentioning
confidence: 99%
“…Procyanidin B2 (epicatechin-(4β-8)-epicatechin; PB2), a phenolic compound, primarily exists in common fruits, including red grapes, cocoa, lindera aggregate and cinnamon (22). PB2 isolated from cinnamon can significantly decline cell viability and accelerate apoptosis in prostate cancer cells, and the proapoptotic effect of PB2 might be associated with caspase-3 activity (23). PB2 is a bioactive component and a potent antioxidant for restoring and maintaining homeostasis (24).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the role of trypsin and cathepsin L in cleavage and activation of spike protein and its binding to ACE2, during the SARS‐CoV infection (Belouzard, Chu, & Whittaker, 2009; Simmons et al, 2011). In this context, cinnamon as a trypsin inhibitor (Gopalakrishnan, Ediga, Reddy, Reddy, & Ismail, 2018; Shahwar, Raza, Shafiq‐Ur‐Rehman, Abbasi, & Atta‐Ur‐Rahman, 2012) could have a therapeutic role against the SARC‐CoV‐2 infection in COVID‐19.…”
Section: Therapeutic Properties Of Natural Productsmentioning
confidence: 99%
“…Studies have shown the role of trypsin and cathepsin L in cleavage and activation of spike protein and its binding to ACE2, during the SARS-CoV infection(Belouzard, Chu, & Whittaker, 2009;Simmons et al, 2011). In this context, cinnamon as a trypsin inhibitor(Gopalakrishnan, Ediga, Reddy, Reddy, & Ismail, 2018;Shahwar, Raza, Shafiq-Ur-Rehman, Abbasi, & Atta-Ur- Rahman, 2012) could have a therapeutic role against the SARC-CoV-2 infection in COVID-19.In CCL 4 and LPS-stimulated rat and mice, cinnamon extracts reduced MDA and increased levels of antioxidant markers catalase and SOD. It also reduced antiinflammatory markers TNF-α/IL-6, reduced phosphorylation of MAPKs (JNK, p38 and ERK1/2), and interfered with NF-κB activation by inhibiting the degradation of IκBα.…”
mentioning
confidence: 99%
“…Cinnamon extract inhibited the growth of K562 cells by terminating the cell cycle at G1 stage and induced apoptosis effectively (Guan et al., 2016). Cinnamon enriched with procyanidin‐B2 decreased the cell multiplication in human prostate cancer cells by inhibiting the activity of 26S proteasome (Gopalakrishnan et al., 2018). Cinnamon with its constituents (procyanidin A), also prevented angiogenesis by regressing the activity of VEGFR2 kinase and by diminishing the VEGF signaling in endothelial cells (Hamidpour et al., 2015).…”
Section: Studies On Cancer With Spices—major Bioactive Compoundsmentioning
confidence: 99%